A qualitative study of patients' perceptions and priorities when living with primary frozen shoulder. Issue 9 (26th September 2013) - Jones, Susan; Hanchard, Nigel; Hamilton, Sharon; Rangan, Amar
Abstract : Objectives: To elucidate the experiences and perceptions of people living with primary frozen shoulder and their priorities for treatment. Design: Qualitative study design using semistructured interviews. Setting: General practitioner (GP) and musculoskeletal clinics in primary and secondary care in one National Health Service Trust in England. Participants: 12 patients diagnosed with primary frozen shoulder were purposively recruited from a GP's surgery, community clinics and hospital clinics. Recruitment targeted the phases of frozen shoulder: pain predominant (n=5), stiffness predominant (n=4) and residual stiffness predominant following hospital treatment (n=2). One participant dropped out. Inclusion criteria: adult, male and female patients of any age, attending the clinics, who had been diagnosed with primary frozen shoulder. Results: The most important experiential themes identified by participants were: pain which was severe as well as inexplicable; inconvenience/disability arising from increasing restriction of movement (due to pain initially, gradually giving way to stiffness); confusion/anxiety associated with delay in diagnosis and uncertainty about the implications for the future; and treatment-related aspects. Participants not directly referred to a specialist (whether physiotherapist, physician or surgeon) wanted a faster, better-defined care pathway. Specialist consultation brought more definitive diagnosis, relief from anxiety and usually self-rated improvement. The main treatment priority was improved function, though there was recognition that this might be facilitated by relief of pain or stiffness. There was a general lack of information from clinicians about the condition with over-reliance on verbal communication and very little written information. Conclusions: Awareness of frozen shoulder should be increased among non-specialists and the best available information made accessible for patients. Our results also highlight the importance of patient participation in frozen shoulder research.